2008
DOI: 10.1016/j.jprot.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the saliva proteome from patients with head and neck squamous cell carcinoma reveals differences in abundance levels of proteins associated with tumour progression and metastasis

Abstract: The objective of this study was to identify differentially expressed proteins in saliva from HNSCC patients compared to a control group. Saliva samples from eight individuals with non-malignant conditions of the head and neck region were employed as a control group and compared to saliva from eight patients with HNSCC using 2D DIGE analysis and subsequent mass spectrometry identification of candidate proteins. Beta fibrin (+ 2.77-fold), S100 calcium binding protein (+ 5.35-fold), transferrin (+3.37-fold), immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 32 publications
4
54
0
3
Order By: Relevance
“…In the same study, cofilin-1 levels were significantly associated with the Gleason score and the presence of lymph node metastasis (38). Furthermore, proteomic analysis of saliva from patients with head and neck squamous cell carcinoma, revealed significantly increased levels of cofilin-1 compared to the control group (39). Additionally, high expression levels of cofilin-1 were associated with large tumor size, high TNM stage, lymph node metastasis, and decreased overall survival in immunohistochemical studies of patients with squamous cell and adenosquamous carcinoma, and adenocarcinoma of the gallbladder (40).…”
Section: Discussionmentioning
confidence: 73%
“…In the same study, cofilin-1 levels were significantly associated with the Gleason score and the presence of lymph node metastasis (38). Furthermore, proteomic analysis of saliva from patients with head and neck squamous cell carcinoma, revealed significantly increased levels of cofilin-1 compared to the control group (39). Additionally, high expression levels of cofilin-1 were associated with large tumor size, high TNM stage, lymph node metastasis, and decreased overall survival in immunohistochemical studies of patients with squamous cell and adenosquamous carcinoma, and adenocarcinoma of the gallbladder (40).…”
Section: Discussionmentioning
confidence: 73%
“…Although serum S100 proteins may have potential implications in various types of cancers, there are still limited clinical applications for S100 proteins, with the only independent prognostic marker being serum S100B in melanoma [52] [53]. The differential reporting of S100 calcium binding protein by Dowling et al and Sewell et al as identified in this review may be secondary to the different sample sources (saliva and tumor tissue, respectively) and the use of control samples from the same patient by Dowling et al [23] [31].…”
Section: Discussionmentioning
confidence: 88%
“…2 of these proteins-S100 calcium binding protein A9 and transferrin were reported as differentially expressed by more than one study, with transferrin [23] [31] reported to be up-regulated in 2 studies, while the differential expression of S100 calcium binding protein A9 was inconsistently reported in 2 studies [23] [31]. A selection of identified proteins will be discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…As the saliva biologically is within an immediate surrounding of the developing tumor the detection of Transferrin might be useful. Many experts thus agreed that it is worth to include Transferrin in a panel of biomarkers for therapeutic monitoring and for early detection of HNSCC (Dowling, 2008). Similarly the iron binding proteins, lactoferrin and transferrin were measured higher in patients with periodontitis, partial dentures and edentulous patients as well as those wearing complete dentures.…”
Section: Transcortinmentioning
confidence: 99%